Molecular Insights into Red Palm Weevil Resistance Mechanisms of Coconut (Cocos nucifera) Leaves - Li Liu; Wei Yan; Bo Liu; Weiquan Qin (Plants, 2024)
Red palm weevil (RPW) (Rhynchophorus ferrugineus) threatens most palm species worldwide. This study investigated the molecular responses of coconut (Cocos nucifera) leaves to RPW infestation through metabolomics and transcriptomics analysis. An RPW insect attack model was developed by placing different RPW larval densitiesin coconut plants and measuring the relative chlorophyll content of different leaf positions and physiological indicators of dysfunction after RPW infestation. The metabolomic changes were detected in the leaves of 10, 20, 30, 40, and 50 days after infestation (DAI) using GC-MS. Certain metabolites (glycine, D-pinitol, lauric acid, allylmalonic acid, D-glucaro-1, 4-lactone, protocatechuic acid, alpha, and alpha-trehalose) were found to be possible indicators for distinct stages of infestation using metabolomics analysis. The influence on ABC transporters, glutathione, galactose, and glycolipid metabolism was emphasized by pathway analysis. Differentially expressed genes (DEGs) were identified at 5, 10, 15, and 20 DAI through transcriptomics analysis of infested coconut leaves, with altered expression levels under RPW infestation. The KEGG pathway and GO analysis revealed enrichment in pathways related to metabolism, stress response, and plant–pathogen interactions, shedding light on the intricate mechanisms underlying coconut–RPW interactions. The identified genes may serve as potential markers for tracking RPW infestation progression and could inform strategies for pest control and management.